Desire for Parenthood and Associated Trends in Czech Lesbian Women - Turcan, Pavel (Sex Med, 2020)
INTRODUCTION: Worldwide, there are more lesbians who chose to have children in the context of a same-sex relationship than ever before. The Czech studies focusing on this issue, including the analysis of methods of conception, are limited. AIM: We aimed to examine the changes over time in the desire of Czech lesbian women for children and to analyze their chosen methods of conception. METHODS: We analyzed retrospectively the personal history of lesbian patients who visited our clinic in the period from 2009 to 2017. Our sample (n = 318) was divided into 2 groups: Group A – our patients between 2009 and 2013, whereas group B comprised our patients from 2013 to 2017. MAIN OUTCOME MEASURES: The outcome of this study is comparing groups A and B, regarding factors associated to parenthood, such as desire to have a child and preferences in methods of conception. RESULTS: We compared group A and group B and obtained the following results: The percentage of homosexual women who did not desire to have a child decreased (22.5% vs 15.6%). Regarding the changes in the preferences in methods of conception among group A and group B, the findings are as follows: a child from a previous relationship (31.2% vs 27.4%), clinically assisted reproduction with an anonymous donor (19.6% vs 30.1%), home intrauterine insemmination with a known donor (24.6% vs 19.2%), clinically assisted reproduction with a known donor (13.1% vs 9.6%), coitus outside the relationship for the purpose of a child conception (9.8% vs 5.5%), home intrauterine insemmination by sperm from an anonymous donor (1.6% vs 4.1%), assisted reproduction performed abroad was selected only in group B (2.7%). CONCLUSIONS: We confirm that the percentage of Czech lesbians who have a child or want to have a child has increased and that several variables regarding the desire for parenthood in the Czech lesbian community are changing over time (eg, methods of conception) mostly in concordance with other Western European countries. Turcan P, Prochazka M, Prochazka P, et al. Desire for Parenthood and Associated Trends in Czech Lesbian Women. Sex Med 2020;8:650–659.